Composición florística y estructura del bosque del predio "El recuerdo", en el cantón Vinces. Año 2018 - Cornejo Serrano, Danny Roberto (2018)
The loss of plant biodiversity in the world, is a serious concurrent problem in all ecosystems and existing plant formations that has increased exponentially in recent years, it is for this reason, that it is highly relevant to make studies regarding the floristic composition and structural of forests. The Abras wetland of Mantequilla, is an area of international importance, RAMSAR category, being located in the position 1 023 in the world, fourth in Ecuador, the same as, it has around its seasonal lagoons remnants of dry semideciduous forest. The cantons involved in the Wetland jurisdiction are: Vinces, Baba, Ventanas, Mocache and Puebloviejo. In the reciento "El Recuerdo" is a remnant of forest, in which, the analysis of the floristic and structural composition of this area was performed, installing 12 sampling units (SU) of 400 m2 for data analysis, in where, 239 individuals with DBH ≥ 7,5 cm were registered, corresponding to 20 families, 35 genera and 38 species (including 2 unidentified). The most important family according to the number of species was: Leguminosae (10 species). Diversity indices (Shannon and Simpson) showed that plot 2 presents diversity of high magnitude (1,03 and 17,10); while, plot 8 has the lowest magnitude in species diversity (0,35 and 1,93). For the value index of ecological importance (IVI) it was known that the species Cochlospermum vitifoloum (bototillo), presented 37,91% in ecological importance; while for the forest value index (IVF) the most important species was Castilla elastica (caucho) (16,47%), because it was one of the species with the largest diameter (≥ 50 cm) that was found in the zone. According to the results, viable and sustainable strategies were created, which could be implemented in the wetland, bringing economic, protection and conservation benefits. Key words: Biodiversity, floristic composition, structure, protection, conservation, wetland.